Study guides

☆☆

Q: How do you solve 2x plus 3 equals 9X equals?

Write your answer...

Submit

Still have questions?

Related questions

2x+3=9x =>3=7x =>3/7=x

2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7

it equals 13X.

2x + 5x - 1 = 9x 7x - 1 = 9x -1 = 9x - 7x -1 = 2x -1/2=x

2x + 9x simplified would be 11x

2x + ? = 9x9x - 2x = 7xso...2x + 7x = 9x

It is 9x

khjgfsddfghjfghjk

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

2x + 24 = 9x - 39= 2x + 63 = 9x= 63 = 7x= x = 9

2x+3=9x-2x -2x3=7x/7 /73/7=x

2x+3=9x 3=9x-2x 3=7x x=3/7

X= -2

44 = 9x +8 36=9x 4=x

2x+5=11 2x=6 x=3

answer is 4 7x+19=-2x+55 +2x +2x 9x+19= 0 55 -19 -19 9x = 36 9 9 =4

7x + 19 = -2x + 55Add 2x to both sides:9x + 19 = 55Subtract 19 from both sides:9x = 36Divide both sides by 9x = 4

9x+6 = 7x+18 9x-7x = 18-6 2x = 12 x = 6

2x + 6 + 9x = 39 11x + 6 = 39 11x = 39 - 6 11x = 33 x = 3

Use the quadratic formula. x = -4.265564 or -0.234436

180=11x+9x. 180 = 20x. 18=2x. 9=x.

Latonia

2x2 - 9x = 18 2x2 - 9x -18 = 0 (2x - 18)(x + 9) x= -9 and 9

You can solve this as a quadratic (it's degree is 2). 9x^2+2x=7 9x^2+2x-7=0 (Hey, a quadratic!) (9x-7)(x+1)=0 Thus, the solutions for x to this problem are -1, and 7/9.

9x-5x-2x = -4 2x = -4 x = -2